(untitled) (Journal of European Studies (JES), 2018)
While negotiations for the accession of some countries to the European Union (EU) are still underway, the European Neighborhood Policy (ENP), initiated in 2004, is working to bring the states neighbouring the EU territory in the east and the south, to a closer economic and security coordination. Further, in 2009 the Eastern Partnership (EaP) program was inaugurated with a particular objective of coordinating with the post-Soviet states. In this context, the Soviet successor states – Belarus, Ukraine, Moldova, Georgia, Armenia and Azerbaijan have been approached, and some instruments of partnership have been signed. On the other hand, these countries also form a part of what Russia perceives as her “near abroad”, whose interests Moscow has tactically aligned with its own through many bilateral accords as well as ventures like the Commonwealth of Independent States (CIS). In 2015, along with Belarus and Kazakhstan, Russia announced the establishment of the Eurasian Economic Union (EEU). In order to compete with the European Union, the organisation aims to incorporate other Eurasian states. Against the backdrop of the stated developments, with the help of the ‘dualistic operational model’, this paper attempts to compare the functionalist and imperialist aspects of the two endeavours (Eastern Partnership and EEU). It questions the viability of the idea of Eastern Partnership. Also, it weighs the possibilities of a confrontation between the EU and Russia, and its repercussions on the concerned states.